INFLAMMATORY MARKERS CRP, FERRITIN, TUMOUR NECROSIS FACTOR ALPHA IN PREECLAMPSIA. - Ms. Shubhangi H Gawade; Dr. Pooja N Joshi; Dr. Gouri A Gulavani; Ms. Farheen Mujawar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Preeclampsia (PE) is one of the most serious pregnancy complications. The worldwide prevalence of PE ranges from 3 to 7% of pregnancies, affecting a total of 8.5 million women worldwide.PE   is responsible for about 18% of maternal deaths and up to 40% of fetal mortality. At this time, PE still lacks a safe and effective therapy, as well as a reliable, early means of diagnosis or prediction.